EPEN-07. EPENDYMOMAS IN INFANCY: UNDERLYING GENETIC ALTERATIONS, HISTOLOGICAL FEATURES AND CLINICAL OUTCOME. (23rd April 2019) - Jünger, Stephanie; Mynarek, Martin; Dörner, Evelyn; Mühlen, Anja zur; Rutkowski, Stefan; von Bueren, Andre; Andreiuolo, Felipe; Pietsch, Torsten
Abstract: Young age represents an adverse prognostic factor in children with ependymomas. Their treatment is challenging since beneficial therapeutic options are limited. As ependymomas are considered a biologically heterogeneous group we aimed to characterize infant ependymomas in respect to their histological and genetic features. We analyzed 28 ependymomas in children younger than 18 months at diagnosis treated according to HIT2000-E protocols in which irradiation was postponed until the age of 18 months. All cases underwent neuropathological review, including immunohistochemical characterization. Genome-wide copy number alterations (CNA) were assessed by molecular inversion probe assays and RELA and YAP1 fusions were detected by RT-PCR and sequencing. All infant ependymomas were anaplastic (WHO grade III). Complete resection was accomplished in 57% of cases. 75% of cases were located in the posterior fossa, all of which showing loss of H3-K27me3, characteristic for PFA ependymomas. CNA analysis showed a stable genome in all cases. No gain of chromosome 1q was observed, an adverse prognostic marker in PFA tumors of older children. After a median follow-up of 5.4 years, 71% relapsed, and 43 % died. Seven ependymomas occurred in the supratentorial region of which in only two cases a complete resection could be achieved. Four tumors carried C11orf95-RELA fusions and two cases typical YAP1-MAMLD1 fusions (one case, not analyzable). The RELA -fused cases did not display CDKN2A loss as an adverse indicator of prognosis in this disease entity. Although 43% of infants with supratentorial ependymomas relapsed, all patients survived (median follow-up, 8.0 years). Infant ependymomas seem to consist of three biological entities: supratentorial tumors carrying RELA or YAP fusions and PFA ependymomas. The latter showed a particularly unfavorable outcome even though chromosome 1q gain was not present. Further biological studies are warranted in these neoplasms to identify prognostic markers and suitable targets for a more effective treatment.